Analysis of Microfaces and Depositional Environment of Limestone in North Isimu Area, Gorontaolo Regency - Robot, Ladya Cheryl; Permana, Aang Panji; Akase, Noviar (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2024)
The geological conditions in the northern part of Lake Limboto vary greatly from the constituent rocks to the working geological structures. Lithological variations consist of volcanic and plutonic rocks to limestone. The area where limestone is widely distributed is in the North Isimu Region, Gorontalo Regency. This research aims to analyze the geological conditions, microfacies and depositional environment of limestone in the North Isimu Region, Gorontalo Regency. The research methods used to achieve this goal consist of field surveys and petrographic laboratory analysis. Field surveys include taking rock samples, taking coordinate points, taking elevation, geomorphological observations, observing geological structures and taking field documentation. Meanwhile, petrographic analysis of rocks uses a polarizing microscope as a tool to follow up megascopic observations. Observation of rock incisions under a microscope using cross nicol and parallel nicol. Based on the results and discussion, it shows that the geomorphology of the research area includes structural hills with sub-parallel river flow patterns. The geological structure of the research area is a descending fault trending northwest-southeast. The research area is divided into four facies, namely foraminifera wackestone, crystalline limestone, foraminifera algae packstone and coralline floatstone. Standard microfacies (SMF) in the North Isimu Region consists of three SMF namely SMF-3, SMF-4 and SMF-5 with two limestone depositional environmental zones namely toe of slope (FZ-3) and slope (FZ-4). FZ-3 was deposited at the end of the foreslope zone and FZ-4 was deposited seaward of the foreslope from the edge of the carbonate debris platform.Keywords: Limestone; Microfacies; Depositional Environment; North Isimu